ESG and firm financial distress in Malaysia: Univariate approach - Mohd Ashari Bakri; Yee-Ee Chia; Jocelyn Mok Pau Chee (The Publisher, 2023)
This study examines the impact of environmental, social, and governance (ESG) assessments on corporate financial distress in the Malaysian context. Specifically, using Malaysian companies listed in DataStream (Kuala Lumpur Stock Exchange main board and second board and ACE market) from 2012 to 2021, we aim to examine which ESG elements have significant impact on mitigating corporate financial distress. Our study shows that among three ESG scores (environmental pillar, social pillar, and governance pillar), the E-score has a negative impact on the likelihood of company financial distress or bankruptcy (Altman z-score). By using a univariate approach, results suggest that environmental concerns (through the Environmental Pillar Score) should significantly improve corporate financial stability and sustainability (by reducing corporate financial distress).